Autosomal dominant polycystic kidney disease in University Clinic of Nephrology and Haemodialysis of Cotonou - LALEYE, Y Anatole; AWEDE, B; AGBOTON, Bruno Leopold; AZONBAKIN, Simon; BIAOU, OLIVIER; SAGBO, G; ADJAGBA, M; AUDREZET, MP (My University, 2012)
Autosomal dominant polycystic kidney disease in University Clinic of Nephrology and Haemodialysis of Cotonou: Clinical and genetical findings: Autosomal dominant polycystic kidney disease (ADPKD) is the most common hereditary kidney disease, but poorly studied in Africa. Its frequency in the University Clinic of Nephrology and Hemodialysis of Cotonou during the ten last years was 7 cases per year with a hospital prevalence estimated at 18 per 1000. The mean age of patients was 47.2 years extending from 29 to 70 years. Males were predominant with a sex ratio of 1.13. Family history was found in 47% of patients. The most common manifestations were lumbar pain (62%), high blood pressure (59%) urinary tract infections (53%), hematuria (46%), and abdominal masses (43%). Hepatic cysts were the most extra renal manifestations, found in 34% of cases. Renal failure was observed in 72% of patients of our series, six of them were under dialysis. Direct sequencing of polycystin 1 gene enabled us to identify some new mutations: 4 nonsense mutations (p.Q2824X exon 23, p.Q1651X exon 15, p.W1666X exon 15, p.R966W exon 12), duplication (c _1761.1745 dup exon 9), a deletion (c.9397+1_9397+8del intron 26) and a deletion-insertion (c.7290_7291delins CTGCA exon 18).
Keywords: Autosomal dominant polycystic kidney disease – Polycystin 1 – Mutations – Renal failure